2022
DOI: 10.7759/cureus.22005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Quality of Life (5-15 Years Post-Thyroidectomy) of Thyroid Carcinoma Patients in Two Tertiary Care Hospitals

Abstract: Early detection of thyroid cancer has reduced mortality and improved survival of patients. Increased detection has raised the incidence of early stage disease. Some physicians underestimate the suffering of these patients due to the concept of "good cancer." The unmet needs of the survivors still need to be addressed. The objective of this paper was to evaluate the long-term quality of life (QOL) of thyroid cancer survivors. MethodsA cross-sectional telephone survey of 211 thyroid cancer survivors who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Nevertheless, symptoms like numbness in hands or feet were reported by 38% of our participants, compared to a mean score of 2.32 ± 1.22. However, the items “problems with your teeth" (48%) and “problems with swallowing solid food" (37%) were more perceived symptoms by our participants, yet shoulder pain (2.04 ± 1.18) and skin problems (2.04 ± 1.18) were more appreciated symptoms by Saudi participants from the Riyadh area [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, symptoms like numbness in hands or feet were reported by 38% of our participants, compared to a mean score of 2.32 ± 1.22. However, the items “problems with your teeth" (48%) and “problems with swallowing solid food" (37%) were more perceived symptoms by our participants, yet shoulder pain (2.04 ± 1.18) and skin problems (2.04 ± 1.18) were more appreciated symptoms by Saudi participants from the Riyadh area [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the majority of patients report higher levels of self-esteem and body image post-thyroidectomy, as the removal of a diseased or abnormal thyroid gland can alleviate anxiety and distress associated with the underlying condition. However, additional research is needed to explore the specific factors contributing to these positive psychological outcomes and to identify potential interventions for those experiencing psychological distress following thyroidectomy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding emotional functioning, patients have fears or concerns about their future health and they feel that they may often be angry, anxious, and fearful [ 10 ]. Performing screening, counseling, and treatment of depression for patients with thyroid cancer is being directed by medical professionals [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study by Wang et al, Li et al, and Nickel et al, the specific type of surgery, total thyroidectomy, was also one of the predictors of a reduction in the QoL score [ 2 , 7 , 17 ]. However, a study done in Saudi Arabia reported that the surgical method did not affect the QoL outcome of patients with thyroid cancer 5-15 years after surgery [ 10 ]. The results are different.…”
Section: Discussionmentioning
confidence: 99%